2019
DOI: 10.1088/1748-9326/ab51a1
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the high solar potential in Africa in a changing climate

Abstract: The African continent faces several challenges and threats: high vulnerability to climate change, the fastest population increase, the lowest degree of electrification and the need for an energy transition towards renewable energies. Solar energy constitutes a viable option for addressing these issues. In a changing climate the efficient implementation of solar capacity should rely on comprehensive information about the solar resource. Here, the newest and highest resolution regional climate simulation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 69 publications
2
20
0
1
Order By: Relevance
“…Given the different responses of different energy sources, complementary energy strategies should be used in different regions. The results of this study are consistent with, and thus reinforce, a number of previous findings over the continent (Sawadogo et al 2019a, b;Soares et al 2019b, andBichet et al 2019), although the magnitude of changes found in this study appear smaller than in previous ones, and some differences are found over specific regions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Given the different responses of different energy sources, complementary energy strategies should be used in different regions. The results of this study are consistent with, and thus reinforce, a number of previous findings over the continent (Sawadogo et al 2019a, b;Soares et al 2019b, andBichet et al 2019), although the magnitude of changes found in this study appear smaller than in previous ones, and some differences are found over specific regions.…”
Section: Discussionsupporting
confidence: 93%
“…At the seasonal scale, most of the Southern African countries are found to possibly experience a decrease in solar irradiance during June-July-August by 2050 (Fant et al 2016). Additionally, Tang et al (2019b) projected a significant increase in solar irradiance in December-January-February over Southern Africa under both the RCP4.5 and RCP8.5 scenarios by 2100 and Soares et al (2019b) found an increase in PV power potential over Southern Africa and a decrease in Eastern Central Africa under the RCP 4.5 and RCP 8.5 scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…For the area B1, the annual wind resource is projected to slightly increase, (under ∼+7%) throughout the 21st century due to a strong spring increase of wind energy, which may reach values of ∼+20% for the ROM runs and values below ∼+10% for the CORDEX-Africa MME. This is in line with Soares et al (2019), who showed that during spring, the surface wind speed and frequency of NACLLJ occurrence is projected to increase. In winter and autumn, the wind energy is projected to be reduced in the B1 area.…”
Section: Future Climate Wind Resourcesupporting
confidence: 91%
“…Previous works (Jerez et al, 2015;Sørland et al, 2018;Bartók et al, 2017) detected inconsistencies in the change signals between RCM projections and those from their driving GCM, which have been related to the way aerosols were represented in the RCM through their impact on the simulated AOD (Gutiérrez et al, 2020;Boé et al, 2020), in particular to their direct and semi-direct effects and their reduced concentrations in the future as long as anthropogenic emissions are projected to decrease. In agreement with these previous findings, insofar as we kept the anthropogenic aerosol emissions unchanged throughout the simulation period, our projections differ from those obtained with the GCM.…”
Section: Discussionmentioning
confidence: 99%
“…From the previous literature, we point out three key features that motivated the present work. The first is the increas-ing use of RCMs to evaluate renewable energy resources and their supply potential (e.g., Jerez et al, 2013Jerez et al, , 2015Jerez et al, , 2019Gil et al, 2019;Soares et al, 2019;van der Wiel et al, 2019). The second is the key role of aerosols regarding the accuracy of the simulated solar resource by climate models (Gaetani et al, 2014;Nabat et al, 2015b;Pavlidis et al, 2020), particularly attributed to their direct and semi-direct effects, which would help to explain the aforementioned discrepancy between GCM and RCM future projections (Boé et al, 2020;Gutiérrez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%